Who is afraid of pirates? An experiment on the deterrence of innovation by imitation - Christoph Engel; Marco Kleine (Max Planck Institute for Research on Collective Goods, 2013)
In the policy debate, intellectual property is often justified by what seems to be a straightforward argument: if innovators are not protected against others appropriating their ideas, incentives for innovation are suboptimally low. Now in most industries for most potential users, appropriating a foreign innovation is itself an investment decision fraught with cost and risk. Nonetheless standard theory predicts too little innovation. Arguably the problem is exacerbated by innovators' risk aversion as well as their aversion against others benefitting from their efforts without contributing to the cost, and without bearing innovation risk. We model the situation as a game and test it in the lab. We find even more appropriation than predicted by standard theory. But the risk and the experience of appropriation does not deter innovation. We find even more innovation than predicted by theory, and actually more than would be efficient. In the lab, the prospect of givingimitators a free lunch does not have a chilling effect on innovation.
Keywords: H41; O31; D63; K11; C91; D62; H23; L17; D22; 330; innovation; imitation; appropriation; patent; fairness of desert